2011
DOI: 10.1209/0295-5075/94/40004
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chaotic scattering in graphene systems

Abstract: Visit the EPL website to read the latest articles published in cutting-edge fields of research from across the whole of physics. Each compilation is led by its own Co-Editor, who is a leading scientist in that field, and who is responsible for overseeing the review process, selecting referees and making publication decisions for every manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 41 publications
9
61
0
Order By: Relevance
“…Among the different electronic Dirac devices, the chaotic Dirac quantum dot (DQD), also called chaotic Dirac billiard (DB), has received a significant highlight [4,18,[24][25][26][27][28][29][30][31][32][33], due to its universal characteristics. In the search for such universal properties, the Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different electronic Dirac devices, the chaotic Dirac quantum dot (DQD), also called chaotic Dirac billiard (DB), has received a significant highlight [4,18,[24][25][26][27][28][29][30][31][32][33], due to its universal characteristics. In the search for such universal properties, the Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the interplay between different types of classical dynamics and relativistic quantum mechanics can lead to surprising phenomena. For example, in open Hamiltonian systems such as graphene quantum dots, previous works revealed that chaos has relatively weaker effects on the quantum scattering dynamics as compared with the nonrelativistic quantum counterpart [77,78]. For example, when the classical dynamics of a quantum dot is integrable or mixed, there are sharp transmission resonances.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, due to the tremendous development of the science of 2D Dirac materials initiated by the experimental realization of graphene [8][9][10][11][12]57,58 , relativistic quantum manifestations of classical chaos 59 have emerged as a new field of study 39,[60][61][62][63][64][65] , with the basic goal to uncover and understand the possible role of chaos played in relativistic quantum systems. From a practical point of view, exploiting the interplay between chaos and relativistic quantum mechanics can lead to novel ideas for developing electronic devices.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The shape of the scattering region is that of the cosine billiard [36][37][38][39] with an upper and a lower hard boundaries at y(x) = W + (M/2)[1 − cos (2πx/L − π)] and y = 0, respectively, for −L/2 ≤ x ≤ L/2. To make the scattering region symmetrical, we choose the lower boundary to be y(…”
Section: Introductionmentioning
confidence: 99%